Research progress and prospects on resource utilization of coal gangue for soil remediation in China - Chengyong LIU; Wenzhe GU; Feng CUI; Yun ZHANG; Yanbin YANG; Fengqi QIU; Chaofeng YUAN; Haixing CHENG; Ming LI (Meitan kexue jishu)
The large-scale, centralized production of coal gangue, a solid waste from coal mining, has become a major challenge to the sustainable development of the coal industry and its ecological balance. Against this background, the ecological restoration and resource utilization of coal gangue is not only crucial for advancing a circular economy but also essential for achieving pollution reduction and carbon emission goals. Based on the analysis of the feasibility of coal gangue solid waste soil utilization, methods and technologies for the polymorphic separation of valuable and harmful components, and technical pathways for coal gangue soil utilization, the basic progress in the resource utilization of coal gangue solid waste by coal enterprises has been summarized. Key technologies for the polymorphic separation of valuable and harmful components in coal gangue have been distilled, and the engineering application models for coal gangue soil utilization and their impact mechanisms on soil ecological functions have been discussed. The results shows that, coal gangue can improve soil structure, enhance water and nutrient retention, support stable beneficial microbial communities, and provide ecological benefits such as increased soil carbon sequestration and reduced greenhouse gas emissions. Techniques like mineral passivation, microbial fixation, and physical separation can mitigate the harmful elements in coal gangue, enabling its beneficial components to be used in soil remediation, thereby reducing environmental risks. This approach offers a practical solution for agricultural soil enhancement and ecological restoration in mining areas. However, the large-scale implementation of coal gangue soil utilization is hindered by challenges such as high modification costs, insufficient long-term stability of heavy metals, and limited regional adaptability. Looking ahead, efforts should focus on addressing these technological barriers, with particular emphasis on integrated applications, low-cost modifications, cross-regional collaboration, and dynamic monitoring of restoration outcomes. A comprehensive utilization model based on “graded classification, directed transformation, and synergistic effect” should be established. Additionally, strengthening policy guidance and building a robust standards system will be key to scaling up coal gangue soil utilization and advancing its industrial development, thus supporting solid waste resource recovery, soil restoration, and the achievement of carbon peaking and carbon neutrality goals.